Distribution of minor and trace metals in lake and sea environments (Antarctica) - ABOLLINO, Ornella; ACETO, Maurizio; SARZANINI, Corrado; MENTASTI, Edoardo; G. Sacchero (1996)
We report the distribution of a series of metals in natural samples collected from Antarctic lakes (Carezza lake no. 3, Edmonson Point lake no. 13C, Inexpressible Island lake no. 9) during the Italian Expeditions in the austral summers 1990/91 and 1991/92. The considered elements are :water, sediments, soil sampled from the surroundings of the lake and algae, for the samplings of 1990/91, and water for the samplings of 1991/92. The determination of the total concentration of the following metals was performed: Al, Ba, Ca, Cd, Co, Cr, Cu, Fe, Mg, Mn, Na, Ni, Pb, Si, Sr, Zn. The determination of some metals, namely Cd, Cu, Fe, Mn, Ni, was also performed on sea water samples collected in 1990/91 on one vertical profile for one off-shore Antarctic Ocean site, and on a series of sampling stations of Ross Sea Bay.